2018
DOI: 10.1038/s41598-018-30468-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the auxin/indole-3-acetic acid (Aux/IAA) gene family in pepper, its characterisation, and comprehensive expression profiling under environmental and phytohormones stress

Abstract: Auxin is an essential phytohormone that plays a crucial role in the growth and development of plants in stressful environments. Here, we analysed the auxin/indole-3-acetic acid (Aux/IAA) gene family, which produces auxin in pepper, and succeeded in identifying 27 putative members containing four conserved domains (I. II. III and IV) in their protein sequences. Sequence analysis, chromosomal mapping and motif prediction of all identified CaAux/IAA genes were performed. It was observed that these genes contained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“… 1 The availability of the plant genome enables us to identify and characterize various gene families under abiotic and biotic stresses. For instance, several gene families have been identified and characterized, such as NAC, 2 , 3 bHLH, 4 MAPK, 5 bZIP, 6–8 GRAS, 9 Aux/IAA, 10 TIFY, 11 FKBP, 12 PEPC, 13 and HSF transcription factors. 14 In addition, plants’ genomes contained plenty of stress-responsive proteins with highly conserved domain 15 , 16 and play critical roles in various plant biological processes during stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 1 The availability of the plant genome enables us to identify and characterize various gene families under abiotic and biotic stresses. For instance, several gene families have been identified and characterized, such as NAC, 2 , 3 bHLH, 4 MAPK, 5 bZIP, 6–8 GRAS, 9 Aux/IAA, 10 TIFY, 11 FKBP, 12 PEPC, 13 and HSF transcription factors. 14 In addition, plants’ genomes contained plenty of stress-responsive proteins with highly conserved domain 15 , 16 and play critical roles in various plant biological processes during stress conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Our results revealed two BAHD genes, tcBAHD13 (a vinorine synthase) and tcBAHD26 (an Omega-hydroxypalmitate Oferuloyl transferase) that were upregulated specifically in resistant cultivars, indicating that these two genes are potentially involved in the P. megakarya fungi response. Although, these results were not validated from qualitative PCR (qPCR), previous studies reported high consistency between the result of RNAseq and qPCR, i.e., in the GASA gene family in soybean (Ahmad et al, 2019) and apple (Fan et al, 2017), extensin genes in tomato (Ding et al, 2020), papain-like cysteine proteases in rice (Niño et al, 2020) and cotton (Zhang et al, 2019), and auxin/indole-3-acetic acid in pepper (Waseem et al, 2018). Nevertheless, a functional study is required to draw a complete conclusion.…”
Section: Discussionmentioning
confidence: 87%
“…In this process, MdIAA45 , MdIAA46 , and MdIAA47 were not anchored to any chromosome due to anomalies in the apple genome sequence (Figure 4A). To determine further the reliability of the screening members, we used protein sequences of IAA members from Arabidopsis (29) (Okushima et al, 2005), Oryza sativa (31) (Jain et al, 2006), Zea mays (31) (Wang et al, 2010), Carica papaya (18) (Liu et al, 2017a), and Capsicum annuum (27) (Waseem et al, 2018) for multiple alignments. The results of a WebLogo annotation showed that the apple IAA protein sequences containing four conserved domains, defined as domains I to IV, had high similarity to their homologs from the other five species (Figure 4B), further confirming the reliability of the MdIAA identification.…”
Section: Resultsmentioning
confidence: 99%